KONSTRUKSI TRADISI KEILMUAN FILSAFAT ISLAM - Mohamad Nur Wahyudi (Bahasa Indonesia, 2023)
Abstract It is essential to reread the history of the tradition of the development of Islamic philosophy in order to study and research further. This is of course based on several assumptions, including the assumption that Islamic philosophy is nothing more than knowledge gained from Greek civilization at that time. Reading the history of Islamic philosophy becomes important when faced with concrete problems such as economic, political, and ethical issues. To respond to assumptions related to the claim that Islamic philosophy is a copy-paste of Greek civilization, further research is needed. Based on the identification made by the author, it was found that historically, the knowledge acquired by Muslims at that time was oriented towards or centered on two major civilizations, namely Greece and Egypt. However, what Muslim scientists and philosophers did at that time was not only copy knowledge from these two civilizations, but they also naturalized knowledge by formulating it based on Islamic sources, namely the Al-Qur'an and Hadith.